Discourse analysis beyond the speech event - Wortham, Stanton Emerson Fisher 1963-; Reyes, Angela (Routledge, 2015)
"Discourse Analysis beyond the Speech Event introduces a new approach to discourse analysis. In this innovative work, Wortham and Reyes argue that discourse analysts should look beyond fixed speech events and consider the development of discourses over time. Drawing on theories and methods from linguistic anthropology and related fields, this book is the first to present a systematic methodological approach to conducting discourse analysis of linked events, allowing researchers to understand not only individual events but also the patterns that emerge across them.Discourse Analysis beyond the Speech Event Provides a method for detailed examination of speech, writing and other communication Introduces students and researchers to the discourse analytic tools and techniques required to analyse the relationships between discourse events Offers explicit guidelines that direct the reader through different stages of discourse analytic research, including worked examples from conversation, magazines and social media Incorporates sample analyses from ethnographic, archival and new media data.This book is essential reading for advanced students and researchers working in the area of discourse analysis"--Provided by publisher.